2021
DOI: 10.1021/acssuschemeng.1c00668
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Recycling of Low-GWP Hydrofluorocarbon/Hydrofluoroolefin Refrigerant Mixtures Using Composite Ionic Liquid–Polymer Membranes

Abstract: The restrictions imposed to the production of highglobal warming potential refrigerant gases have boosted the search of novel separation processes for the selective recovery of hydrofluorocarbons (HFCs) and hydrofluoroolefins (HFO) from exhausted refrigerant mixtures. Membrane materials functionalized with ionic liquids can offer an effective techno-economical response to the challenging separation of HFC/HFO blends. In this work, we provide for the first time a thorough characterization of the gas solubility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…Pebax membranes functionalized with the ILs [C 2 C 1 Im][SCN] and [C 2 C 1 Im][BF 4 ] were tested for the separation of the refrigerant R-410A (a near-azeotropic system of the HFCs R-32 and R-125), showing improvement in the permeability towards R-32 and of the R-32/R-125 selectivity, relatively to the neat polymer membranes [111]. Additionally, CILPMs were prepared by functionalizing Pebax membranes with SO 3 ], and [C 2 C 1 Im][N(CF 3 SO 2 ) 2 ] and were tested for the solubility and permeation of R-32, R-134a, and the HFO R-1234yf [112]. In this study, the CILPM based on [C 2 C 1 Im][BF 4 ] showed higher permeability towards the HFCs R-32 and R-134a compared to the HFO R-1234yf, demonstrating to be useful for the separation of HFC/HFO blends [112].…”
Section: Gas Separation Processes Using Fluorinated Ionic Liquids-bas...mentioning
confidence: 99%
“…Pebax membranes functionalized with the ILs [C 2 C 1 Im][SCN] and [C 2 C 1 Im][BF 4 ] were tested for the separation of the refrigerant R-410A (a near-azeotropic system of the HFCs R-32 and R-125), showing improvement in the permeability towards R-32 and of the R-32/R-125 selectivity, relatively to the neat polymer membranes [111]. Additionally, CILPMs were prepared by functionalizing Pebax membranes with SO 3 ], and [C 2 C 1 Im][N(CF 3 SO 2 ) 2 ] and were tested for the solubility and permeation of R-32, R-134a, and the HFO R-1234yf [112]. In this study, the CILPM based on [C 2 C 1 Im][BF 4 ] showed higher permeability towards the HFCs R-32 and R-134a compared to the HFO R-1234yf, demonstrating to be useful for the separation of HFC/HFO blends [112].…”
Section: Gas Separation Processes Using Fluorinated Ionic Liquids-bas...mentioning
confidence: 99%
“…HFCs are commonly used as refrigerants in domestic and commercial cooling systems. These compounds account for 2%–3% of the global greenhouse gas (GHG) emissions 46 which prompted the Kigali Amendment to the Montreal Protocol to recommend cutting the global HFC emissions by 80%–85% by 2047 47 . Therefore, it is desirable for these HFCs to be recycled so that the amount of newly manufactured HFC molecules can be minimized.…”
Section: Prediction Of Hfc Solubility In Ilmentioning
confidence: 99%
“…These compounds account for 2%-3% of the global greenhouse gas (GHG) emissions 46 which prompted the Kigali Amendment to the Montreal Protocol to recommend cutting the global HFC emissions by 80%-85% by 2047. 47 Therefore, it is desirable for these HFCs to be recycled so that the amount of newly manufactured HFC molecules can be minimized. However, recycling through separation of HFCs pose a significant challenge as these are azeotropic or closeboiling mixtures that often behave as single fluids.…”
Section: Prediction Of Hfc Solubility In Ilmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 In recent years, researchers have prepared mixed matrix membranes (MMMs) by filling dopants into polymer substrates, and tried to overcome the trade-off effect by taking advantage of the respective performance advantages of dopants materials and polymer materials. 6 Up to now, the commonly used dopants mainly include nano metal oxides (Al 2 O 3 , SiO 2 , TiO 2 ), 7 carbon nanotubes (CNTs), 8 graphene oxide (GO), 9,10 MOFs, 11,12 ionic liquids, 13,14 etc. Pebax, as a common membrane matrix, has often been used to prepare MMMs due to its special properties.…”
Section: Introductionmentioning
confidence: 99%